INCLUSIVE EDUCATION AS A FACTOR OF ENSURING EQUALITY IN EDUCATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the article, inclusive education is not only among disabled children, but also based on a healthy lifestyle, as well as ensuring equality in education, as well as creating favorable opportunities for students with different levels of mastery of subjects at school, even among children raised in the family, the results of which students can have a positive influence on each other through this. , the relevance of inclusive education, the fact that disabled children should have equal opportunities in education with other children, the need to introduce a form of education that creates optimal educational conditions for disabled children, the relevance of inclusive education in the changing social demand for the education of disabled children and state policy, the field of education of disabled children, its content -in essence, issues such as children with disabilities having the opportunity to study together with their healthy peers in general education schools, to be accepted into their community, to develop according to their abilities and to have the perspective of participation in the life of society are interpreted.